Etika Islam dan Pengembangan Umkm: Dampaknya Terhadap Perekonomian Mahasiswa dan Kesejahteraan Mahasiswa STAI Kuala Kapuas - Bidin (AL-IBNOR, 2025)
The development of Micro, Small and Medium Enterprises (MSMEs) among students has great potential in improving the local economy and social welfare. In this context, the application of Islamic ethics plays an important role in the sustainable management of MSMEs. This research aims to analyze the application of Islamic ethical principles in managing MSMEs by STAI Kuala Kapuas students and its impact on the economy and their welfare. The research method used was interviews and observations of students involved in managing MSMEs on campus. The research results show that students apply Islamic ethical principles such as honesty in transactions, halal financial management, and the use of zakat and waqf. This practice not only improves the quality of their business, but also makes a positive contribution to the welfare of the people and the blessings of the business. The application of Islamic ethics in managing MSMEs has been proven to have a positive impact on both business development and improving the welfare of students themselves. It is hoped that this research can become a reference for developing sustainable Islamic ethics-based MSMEs among students in Indonesia.